A Cluster Randomized Trial of Promoting Alternative Thinking Strategies (PATHS®) With Swedish Preschool Children - Eninger, Lilianne; Ferrer-Wreder, Laura; Eichas, Kyle; Olsson, Tina M.; Hau, Hanna Ginner; Allodi, Mara Westling; Smedler, Ann-Charlotte; Sedem, Mina; Gull, Ingela Clausén; Herkner, Birgitta (Frontiers in Psychology, 2021)
The preschool edition of Promoting Alternative THinking Strategies (PATHS®) is a school-based, teacher implemented universal intervention developed in the United States designed to promote social emotional competence (SEC) in children as a foundation for improved mental health. PATHS is delivered as a curriculum and it is based on theories and research regarding SEC, brain development, and optimal school environments. A majority of children in Sweden attend preschool, which is government-subsidized and follows a national curriculum focusing on both academic and social emotional learning. However, there is not so much focus on formal instruction nor manual-based lessons. The purpose of this study was to assess the short-term (pre- to post-test) effects of PATHS in the Swedish preschool setting. Using a two-wave cluster randomized trial with multi-method and informant assessment (N = 285 4 and 5-year-old Swedish children; n = 145 wait-list control; n = 140 intervention; K = 26 preschools; k = 13 intervention; k = 13 control) we assessed changes in child emotional knowledge, emotional awareness, social problem solving, prosocial play, inhibitory control, and working memory using structural equation modeling (SEM). We included schools with at least one classroom of 4–5-year-old children from three municipalities. We excluded open preschools, parent cooperative preschools, and family day homes. After random assignment, schools were informed of condition assignment. Research team members were not blind to assignment. We hypothesized that relative to children in control schools, children in intervention schools would evidence improvements in social emotional competence as well as other outcomes. Children in PATHS, relative to children in the control, evidenced improvements in working memory and prosocial play, but also showed an increase in hyperactive behaviors. Girls in PATHS, relative to girls in the control, showed improvement in emotional knowledge and reduced anxiety. These results are considered in light of efforts to promote positive development and mental health. The trial registration number at ClinicalTrials.gov is NCT04512157. Main funding was from Swedish Council for Working Life and Social Research, the Swedish Research Council, Formas, and VINNOVA (dnr: 259-2012-71).